PEMBERIAN MINYAK IKAN LEMURU (Sardinella longiceps) SEBAGAI ANTI DISLIPIDEMIA MELALUI PENINGKATAN HDL PADA TIKUS WISTAR - Sri Wahjuni (Jurnal Kimia (Journal of Chemistry), 2011)
Changes in consumption behaviour to instant food can cause various health problems, such as obesity, dislipidemia, and atheroschlerosis. A study was conducted to investigate sardinella longiceps oil as anti dislipidemia through increasing HDL-C levels.This is a true experimental with randomized pre and posttest control group designs, emplyoying 50 Wistar rats grouped into five groups, i.e. control group (0% fish oil), treatment 1 group (10% fish oil), treatment 2 group (15% fish oil), treatment 3 group (20% fish oil), and treatment 4 group (25% sardinella longiceps oil). This research observed that intake of 20% sardinella longiceps oil resulted in the higest significant increase of HDL-C of 22.78 % (from 55.97 ±1.25 to 68.72 ± 6.25 mg/dL) for dislipidemia study. Therefore, it can be concluded that intake of sardinella longiceps oil in Wistar rat acts as anti dislipidemia by increasing the HDL-C levels. Further research is required to determine whether the application of sardinella longiceps on human will result in a simillar way, as anti inflammation and anti dislipidemia.